Testing Semi-strong Form Efficiency of Stock Market (The Pakistan Development Review, 2001)
The efficient market hypothesis suggests that stock markets are “informationally efficient”. That is, any new information relevant to the market is spontaneously reflected in the stock prices. A consequence of this hypothesis is that past prices cannot have any predictive power for future prices once the current prices have been used as an explanatory variable. In other words the change in future prices depends only on arrival of new information that was unpredictable today hence it is based on surprise information. Another consequence of this hypothesis is that arbitrage opportunities are wiped out instantaneously. Empirical tests of the efficient market hypothesis actually test for these consequences in various ways. Some of them have been summarised in earlier chapters. These tests generally could not conclusively accept the random-walk hypothesis of stock returns even when GARCH effects were accounted for. Many studies have found empirical regularities that are contrary to the efficient market hypothesis. For example, the monthly, weekly and daily returns on stocks tend to exhibit discernable patterns, such as seasonal affects, month of the year affect, day of the week affect, hourly affect etc. In case of Pakistan’s stock markets too such affects are identified. Such as the Ramadan affect [see Hussain and Uppal (1999)], seasonal effects and day of the week affect. Further, the wide spread use of “technical analysis” among stock traders and their ability to predict to some extent the direction of movements in the prices of individual stocks over medium term testifies to the existence of patterns and seasonal trends.